دراسة تأثير بعض عمليات التقليم الصيفي(الأخضر) في كمية الإنتاج ونوعيته لصنفي العنب الحلواني والبلدي - محفوض محمد; جراد علاء الدين; ديوب رباب (Latakia University Journal -Biological Sciences Series, 2013)
تمت دراسة تأثير بعض عمليات التقليم الصيفي(الأخضر) في نمو صنفي العنب المحليين حلواني وبلدي التابعين للنوع .Vitis vinifera L, وإنتاجهما أُجريت الدراسة في مزرعة خاصة في منطقة القدموس خلال العام 2012, على شجيرات عنب مرباة على أسلاك من الصنفين المذكورين, وشملت 7 معاملات (1- شاهد, 2- تفريد, 3- تفريد وقصف, 4- تفريد وقصف وتفريع, 5- تفريد وتفريع, 6- تفريد وتفريع وتوريق, 7- تفريد وتوريق). أظهرت النتائج تأثير عملية القصف في تحسين وزن العنقود والثمرة وذلك نتيجة تأثيرها في تحسين نسبة العقد الأمر الذي انعكس إيجاباً على إنتاج الشجيرة وعلى الصنفين موضوع الدراسة, كما حسنت عملية التفريد فقط نسبة المواد الصلبة الذائبة الكلية بعكس بقية العمليات المنفذة, كما أدت عمليتا القصف والتفريع دوراً في زيادة نسبة الحموضة الكلية. This research was carried out to study the effect of summer pruning on the growth and production of two grape varieties Vitis vivifera L. Halwani and Baladdi. The study was conducted in Kadmous during 2012 growing season on two varieties of grape trees reared on wiredraw. Seven treatments were used: 1- control, 2- shoot thinning, 3- shoot thinning and hedging, 4- shoot thinning and axillary shoot removal, 5- shoot thinning and axillary shoot removal, 6- shoot thinning and axillary shoot removal and leaf removal, 7- shoot thinning and leaf removal. Results show that hedging improves weight of cluster and berry due to the increase in fruit set percentage which leads to an increase in grape production. Shoot thinning increases TSS yet other processes have negative effects: the hedging process increases acid titration in the Baladdi cultivar but in the Halwani cultivar hedging and axillary shoot removal increases acid titration